LabVIEW-based impedance biosensing system for detection of avian influenza virus - Benhua, Zhang; Wang, Ronghui; Wang, Yixiang; Li, Yanbin (International Journal of Agricultural and Biological Engineering, 2016)
In order to detect the multiple avian influenza viruses (AIVs) rapidly, specifically and sensitively, a LabVIEW and microelectrode array-based impedance biosensor was developed and demonstrated. A laptop with LabVIEW software was used to generate excitation signals at different frequencies with an audio card and measure the impedance of target viruses through a data acquisition card. The audio card of the laptop was used as a function generator, while a data acquisition card was used for data communication. A virtual instrument was programmed with LabVIEW to provide a platform for impedance measurement, data processing, and control. Six interdigitated microelectrodes were placed at the bottom of six wells on a microplate to form six sensors for different AIVs and controls. Then, AIV specific ligands were immobilized on the microelectrode surface to capture target viruses. To enhance the sensitivity, AIV specific aptamers conjugated gold nanoparticles and thiocyanuric acid were employed to form a network structure and used as an amplifier. Results of the measured impedance were compared with a commercial IM6 impedance analyzer, and the error was less than 5%. The developed biosensor was portable with the sensitivity and specificity for applications to on-site or in-field rapid screening of avian influenza viruses. Keywords: biosensor, impedance detection, avian influenza virus, LabVIEW DOI: 10.3965/j.ijabe.20160904.1704 Citation: Zhang B H, Wang R H, Wang Y X, Li Y B. LabVIEW-based impedance biosensing system for detection of avian influenza virus. Int J Agric & Biol Eng, 2016; 9(4): 116－122.